MCC950, a Selective NLRP3 Inhibitor, Attenuates Adverse Cardiac Remodeling Following Heart Failure Through Improving the Cardiometabolic Dysfunction in Obese Mice - Wang, Menglong; Zhao, Mengmeng; Yu, Junping; Xu, Yao; Zhang, Jishou; Liu, Jianfang; Zheng, Zihui; Ye, Jing; Wang, Zhen; Ye, Di; Feng, Yongqi; Xu, Shuwan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Obesity is often accompanied by hypertension. Although a large number of studies have confirmed that NLRP3 inhibitors can improve cardiac remodeling in mice with a normal diet, it is still unclear whether NLRP3 inhibitors can improve heart failure (HF) induced by pressure overload in obese mice. The purpose of this study was to explore the role of MCC950, a selective NLRP3 inhibitor, on HF in obese mice and its metabolic mechanism. Obese mice induced with a 10-week high-fat diet (HFD) were used in this study. After 4 weeks of HFD, transverse aortic constriction (TAC) surgery was performed to induce a HF model. MCC950 (10 mg/kg, once/day) was injected intraperitoneally from 2 weeks after TAC and continued for 4 weeks. After echocardiography examination, we harvested left ventricle tissues and performed molecular experiments. The results suggest that in obese mice, MCC950 can significantly improve cardiac hypertrophy and fibrosis caused by pressure overload. MCC950 ameliorated cardiac inflammation after TAC surgery and promoted M2 macrophage infiltration in the cardiac tissue. MCC950 not only restored fatty acid uptake and utilization by regulating the expression of CD36 and CPT1β but also reduced glucose uptake and oxidation via regulating the expression of GLUT4 and p-PDH. In addition, MCC950 affected the phosphorylation of AKT and AMPK in obese mice with HF. In summary, MCC950 can alleviate HF induced by pressure overload in obese mice via improving cardiac metabolism, providing a basis for the clinical application of NLRP3 inhibitors in obese patients with HF.